RESEARCH LEARNING PROGRAM STRATEGY AS AN EFFORT TO IMPROVE THE QUALITY OF EDUCATION - Umi Fatimah; A. Fatah Yasin; Muhammad Walid (STKIP Pesisir Selatan, 2026)
This study aims to describe the implementation strategy of the Research-Based Learning Program at MA Model Zainul Hasan Genggong Probolinggo and to analyze its impact on strengthening the school’s academic ecosystem and students’ competency development. This study employs a qualitative approach with a descriptive research design. Data were collected through observation, in-depth interviews, and documentation studies, involving the principal, vice principal for curriculum, research supervisors, and students as research subjects. Data analysis was conducted interactively through data reduction, data display, and conclusion drawing, while data validity was ensured through source and technique triangulation. The results indicate that the Research-Based Learning Program is implemented systematically through academic literacy habituation, integration of minor research into classroom learning, tiered research implementation each semester, project-based and product-based learning approaches, multi-aspect-based assessment, and appreciation through research competency graduation schemes. This program has a positive impact on strengthening the school’s academic culture, enhancing teacher professionalism, and developing students’ competencies in cognitive, affective, and psychomotor domains. This study recommends strengthening collaboration with higher education institutions and conducting continuous evaluation to ensure the sustainability and quality of the research program in schools.